2013
DOI: 10.1097/aog.0b013e3182a9bf42
|View full text |Cite
|
Sign up to set email alerts
|

Disclosing a Diagnosis of Cancer

Abstract: Objective To characterize gynecologic oncology patients’ perceptions of the process of disclosure of cancer diagnosis. Methods We surveyed 100 gynecologic oncology patients between December 2011 and September 2012. An 83-item tool based on three validated assessment tools evaluated patient-centered factors, physician behavior and communication skills, and environmental factors. Associations between patients’ satisfaction and these variables were analyzed using Wilcoxon rank-sum, Kruskal-Wallis, and Spearman’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“… 19 Dissatisfaction with this topic is an important cause of complaints and lawsuits against doctors and health care institutions. 14 19 20 In line with this, Kuroki et al 16 and Alkazaleh et al 18 showed that the patient's degree of satisfaction with communicating bad news was not completely related to the severity of the malignant neoplasm or fetal malformations, respectively, but to the physicians' attitudes. 16 18 …”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“… 19 Dissatisfaction with this topic is an important cause of complaints and lawsuits against doctors and health care institutions. 14 19 20 In line with this, Kuroki et al 16 and Alkazaleh et al 18 showed that the patient's degree of satisfaction with communicating bad news was not completely related to the severity of the malignant neoplasm or fetal malformations, respectively, but to the physicians' attitudes. 16 18 …”
Section: Resultsmentioning
confidence: 87%
“…When concerning gynecological cancer diagnosis, most of the time, it is announced by physicians who are not specialists in oncology, reinforcing the importance of improving communication skills for medical professionals of all areas. 16 Another rare and specific situation in ob-gyn is the communication of cancer diagnosis during a pregnancy, because situations like this contrast the extremes of life: possible terminality versus the development of a new infant. The approach of these patients requires a multidisciplinary team, and communication must be done by a trained, preferably more experienced, professional.…”
Section: Resultsmentioning
confidence: 99%
“…Revealing a diagnosis of cancer is an art as is discussing the treatment options that follow. The discussion should be tailored to the individual with the involvement of family members, adapted to different patient needs [16]. The offer of physical treatment is considered the easiest discussion.…”
Section: Diagnostic Disclosure and Breaking Bad Newsmentioning
confidence: 99%
“…Eleven (28.2%) studies employed validated instruments to assess PCC. They included: Endometriosis Care Questionnaire [61, 62], Perceptions of Family Centred Care – Parents and Perceptions of Family Centred Care – Staff [27], Patient Expectations and Satisfaction with Prenatal Care Instrument [41], Patient Perception of Patient Centred Care [64], Women Centred Care Pregnancy Questionnaire [44, 40], Patient Assessment of Chronic Illness Care [54], Communication Assessment Tool [50], Wake Forest Trust Scale [50], Global Rating Scale [53], Japanese Measure of Processes of Care for Service Providers, and Japanese Measure of Beliefs about Participation in Family Centred Service [48]. One study validated a new PCC instrument, the Person Centred Maternity Care Tool [34].…”
Section: Resultsmentioning
confidence: 99%
“…These were captured via validated instruments, qualitative interviews, or non-validated surveys created specifically for the study, and were captured either following a PCC intervention or regular consultation. Patient ratings of PCC were found to be positively correlated with health-related quality of life [61], care satisfaction [44, 47, 50], disease understanding [54], sense of control during birth [44, 47], and clinical outcomes including pain reduction [64], functional recovery [64], and physiological child birth [33]. Patient ratings of PCC were negatively correlated with perceived consequences of illness [54].…”
Section: Resultsmentioning
confidence: 99%